Minimum Inhibitory Concentration (MIC) and minimum bactericidal concentration of beluntas leaf ethanol extract against streptococcus mutans - Elin Septiani; Natallia Pranata; Vinna K. Sugiaman (DiscoverSys Inc., 2022)
bjective: The purpose of this study was to determine the exact values of MBC (Minimum Bactericidal Concentration) and MIC (Minimum Inhibitory Concentration) of beluntas leaf extract against Streptococcus mutans colonies. Material and Methood: This study used Streptococcus mutans ATCC 25175 and ethanol extract of beluntas leaves with concentrations: 250 g/ml, 125 g/ml, 62.5 g/ml, 31.3 g/ml, 15.6 g/ml, 7.8 g /ml, 3.9 g/ml and 1.95μg/ml. This study used two methods, Broth Microdilution and Total Plate Count techniques as the designated method for the purpose of counting bacteria. Furthermore, the data analysis test was carried out to analyze normality using the Kolmogorov-Smirnov test. If the data distribution shows normal, then one way ANOVA parametric test is performed to determine the significance between the beluntas leaf extract and the number of streptococcus mutans bacteria, which will then be further examined using the Post-Hoc Test with the Tuckey method to find out which dataset is the most significantly different in among others. Results: The beluntas leaf extract showed significant bacterial properties against Streptococcus mutans (P-Value = 0.00) which was expressed through definite MBC and MIC values. The results showed that the MIC and MBC values were 62.5 g/ml and 125 g/ml, respectively against Streptococcus mutans colonies. Conclusion: The conclusion of this study was that the ethanol extract of the leaves of beluntas (Pluchea Indica L) showed antibacterial properties as indicated by the MIC value at a concentration of 62.5μg/ml and the MBC at a concentration of 125μg/ml against streptococcus mutans.